This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 0: J ( x ) = s n =0 (-1) n n !(1 + + n ) p x 2 P 2 n + . Prove that J +1 ( x ) = J 1 ( x )-2 J ( x ) . 4. ind the Frst three non-zero terms in a series expansion about x = 0 of 2 linearly independent solutions to: 3 xy + (2-x ) y -y = 0 , x > . * Instructor: Patrick De Leenheer....
View Full Document
This note was uploaded on 09/12/2011 for the course MAP 4305 taught by Professor Deleenheer during the Summer '06 term at University of Florida.
- Summer '06